Digital learning platform for cultural heritage: new normal tourism for community - Sakkarin Sapu; Amphol Aphathanakorn; Ratanachote Thienmongkol (Journal of Cultural Heritage Management and Sustainable Development, 2024)
Purpose This study aimed to (1) elucidate the results of a social outcomes assessment and socio-spatial return analysis of a social innovation village (SIV) program in Thailand, (2) develop a social return on investment (SROI) tool for a digital learning platform of cultural heritage and (3) propose the application of an SROI calculator for policy decision-making. Design/methodology/approach SROI methodology was applied to analyze data from a sample of 110 individuals from the SIV in the Tha Ruea community, Nakhon Phanom province, Thailand, which is renowned for musical instrument making, to assess the social innovation objectives. Findings Improvement in the grassroots economy led to increased income, translating to assessment outcomes and social values within the tourism community. Social and digital media platforms link physical and digital spaces to facilitate interactive learning and online tourism in the community. Research limitations/implications Since the COVID-19 pandemic led to a pronounced economic decline, especially in the tourism sector, the results only partially capture the actual benefits of SROI. To address the challenge of adapting the ecosystem of local tourism into the alternative market, training programs are recommended, including upskilling and new-skilling courses offered by state agencies, to support this technological trend. Originality/value This research illustrates how an integrative platform between digital technology and cultural heritage can address the significant shift in tourism behavior and promote a new era of cultural heritage tourism in virtual and physical spaces.
Keywords: Diverse Aspects of Tourism Research; Museums and Cultural Heritage; Religious Tourism and Spaces